The Innovation Gap between the Polish Economy and the European Union - Edyta Dworak (Comparative Economic Research. Central and Eastern Europe, 2020)
Knowledge and innovations are considered to be among the most important factors that determine the pace and quality of economic growth. Therefore, Poland is facing a serious challenge to effectively transform its economy into an innovative economy capable of competing with the most developed countries. The aim of the paper is to present the results of analysis aimed at estimating the innovation gap between Poland and the European Union countries on the basis of the Summary Innovation Index (SII), which was developed by the European Commission within the European Innovation Scoreboard (EIS) in the years 2010-2018. It reviewed the literature on the innovativeness of economies and the innovation gap. Descriptive analysis, statistical data analysis and comparative analysis methods were applied. Statistical data from the European Innovation Scoreboard 2019 were used. The paper formulates a research thesis that assumes that the level of innovativeness of the Polish economy in the analyzed period remained at a lower level than the EU average and therefore there is still an innovation gap between the Polish economy and the average for European Union countries. The results of the analysis confirm this thesis.
Keywords: O30; O31; O33; O43; 330; innovation; innovativeness; innovation gap; European InnovationScoreboard (EIS); Summary Innovation Index (SII)